Dichorionic twin trajectories: the NICHD Fetal Growth Studies - GRANTZ, Katherine L. (Am J Obstet Gynecol, 2016)
BACKGROUND: Systematic evaluation and estimation of growth trajectories in twins require ultrasound measurements across gestation, performed in controlled clinical settings. Currently there are few such data for contemporary populations. There is also controversy about whether twin fetal growth should be evaluated using the same benchmarks as singleton growth. OBJECTIVES: Our objective was to empirically define the trajectory of fetal growth in dichorionic twins using longitudinal two-dimensional ultrasonography and to compare the fetal growth trajectories for dichorionic twins with those based on a growth standard developed by our group for singletons. STUDY DESIGN: A prospective cohort of 171 women with twin gestations was recruited from eight U.S. sites from 2012 to 2013. After an initial sonogram at 11w0d–13w6d where dichorionicity was confirmed, women were randomized to one of two serial ultrasonology schedules. Growth curves and percentiles were estimated using linear mixed models with cubic splines. Percentiles were compared statistically at each gestational week between the twins and 1,731 singletons, after adjustment for maternal age, race/ethnicity, height, weight, parity, employment, marital status, insurance, income, education and infant sex. Linear mixed models were used to test for overall differences between the twin and singleton trajectories using likelihood ratio tests of interaction terms between spline mean structure terms and twin-singleton indicator variables. Singleton standards were weighted to correspond to the distribution of maternal race in twins. For those ultrasound measurements where there were significant global tests for differences between twins and singletons, we tested for week-specific differences using Wald tests computed at each gestational age. In a separate analysis, we evaluated the degree of reclassification in small for gestational age, defined as below the 10(th) percentile that would be introduced if fetal growth estimation for twins was based upon an unweighted singleton standard. RESULTS: Women underwent a median of 5 ultrasounds. The 50(th) percentile abdominal circumference and estimated fetal weight trajectories of twin fetuses diverged significantly beginning at 32 weeks, while biparietal diameter in twins was smaller from 34 through 36 weeks. There were no differences in head circumference or femur length. The mean head circumference/abdominal circumference ratio was progressively larger for twins compared with singletons beginning at 33 weeks, indicating a comparatively asymmetric growth pattern. At 35 weeks, the average gestational age at delivery for twins, the estimated fetal weights for the 10(th), 50(th) and 90(th) percentiles were 1960, 2376, and 2879 g for dichorionic twins and 2180, 2567, and 3022 g for the singletons. At 32 weeks, the initial week when the mean estimated fetal weight for twins was smaller than that of singletons, 34% of twins would be classified as small for gestational age using a singleton, non-Hispanic white standard. By 35 weeks, 38% of twins would be classified as small for gestational age. CONCLUSIONS: The comparatively asymmetric growth pattern in twin gestations, initially evident at 32 weeks, is consistent with the concept that the intrauterine environment becomes constrained in its ability to sustain growth in twin fetuses. Near term, nearly 40% of twins would be classified as small for gestational age based on a singleton growth standard.